Diversity, abundance and conservation of birds in an agroecosystem in the Ica desert, Peru - Salinas, Letty (2006)
Present work investigates the impact of the agricultural activity in the Peruvian coast on the biodiversity of birds. The study includes the monitoring of birds in asparagus and grapes farms of Ica valley, from January-2004 to January-2006. We evaluated eight types of habitats distributed in a total of 1288 has. Throughout the period of study we registered 93 species of birds. The abundance, richness and diversity were greater in the summers. The greater abundance happened in the habitats of land of asparagus, river brushwood and live fences. The greater richness and diversity happened in January-2006 in alfalfa cultures with huarangos and live fences. The most abundant species were the residents, as Zenaida meloda (6,6 ind./it has), Pygochelidon cyanoleuca (5,9) and the migratory Hirundo rustica (5,9). We registered 12 migratory species. From the conservationist point of view, the number of species catalogued in some degree of threat, at national and international level, is very high. We can emphasize the vulnerable Xenospingus concolor, the Peruvian endemic Colaptes atricollis and the species of desert Geositta peruviana, Sporophila simplex and Burhinus superciliaris. This study demonstrates the importance of agroecosystems in the conservation of the Peruvian Coastal Desert biodiversity, in particular if the enterprise carries out a policy of respect to environment.